2005
DOI: 10.1165/rcmb.2005-0056oc
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of Eosinophil Cationic Granule Proteins on IMR-32 Nerve Cell Signaling and Survival

Abstract: Activated eosinophils release potentially toxic cationic granular proteins, including the major basic proteins (MBP) and eosinophil-derived neurotoxin (EDN). However, in inflammatory conditions including asthma and inflammatory bowel disease, localization of eosinophils to nerves is associated with nerve plasticity, specifically remodeling. In previous in vitro studies, we have shown that eosinophil adhesion to IMR-32 nerve cells, via nerve cell intercellular adhesion molecule-1, results in an adhesion-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
0
27
1
1
Order By: Relevance
“…Previous studies and our own preliminary studies indicated that co-culture of eosinophils with IMR32 cells did not lead to significant apoptosis of either the nerves or the eosinophils when they were maintained in coculture for as long as 96 h (12). Indeed, we have shown that eosinophils and their degranulation proteins protect IMR32 cells from apoptosis (52,53). Second, to avoid potential contamination by gene products contained within eosinophils, mRNA extracted from eosinophils was subjected to RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and our own preliminary studies indicated that co-culture of eosinophils with IMR32 cells did not lead to significant apoptosis of either the nerves or the eosinophils when they were maintained in coculture for as long as 96 h (12). Indeed, we have shown that eosinophils and their degranulation proteins protect IMR32 cells from apoptosis (52,53). Second, to avoid potential contamination by gene products contained within eosinophils, mRNA extracted from eosinophils was subjected to RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although a possible involvement of endogenous autacoids cannot be completely ruled out in the present study because certain potent mediators (e.g., PGE 2 or PGI 2 ) may still be released from isolated neurons or from nonneuronal satellite cells present in the culture (25,39,49), other potential contributing factors should also be considered. For example, it is possible that the sustaining action of MBP is related to cascades of intracellular signaling events triggered by the cationic protein in these neurons (37). In addition, a recent study has further revealed that the binding of MBP with certain specific cell-surface receptors plays an important role in its cytostimulatory and cytotoxic properties (18), which may explain, perhaps in part, why the sensitizing effect on the pulmonary neurons in the present study persisted even after MBP was completely washed out of the recording chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the level of eosinophils in the blood of exposed mice can be associated with inflammation in the respiratory systems, allergy and asthma (Morgan et al 2005). According to Kurosky et al (2009), eosinophils are granulocytic leucocytes that function in diverse inflammatory and immunoregulatory processes.…”
Section: Discussionmentioning
confidence: 99%